2021
DOI: 10.3389/fphar.2021.692424
|View full text |Cite
|
Sign up to set email alerts
|

8-Methoxypsoralen has Anti-inflammatory and Antioxidant Roles in Osteoarthritis Through SIRT1/NF-κB Pathway

Abstract: Osteoarthritis (OA) is mainly manifested by joint pain, stiffness and mobility disorder, which is the main cause of pain and disability in middle-aged and elderly people. In this study, we aimed to explore the role and mechanism of 8-Methoxypsoralen (8-MOP) in the OA model both in vitro and in vivo. The rat chondrocytes were treated with IL-1β, and the proliferation, apoptosis, inflammatory reactions and oxidative stress responses were determined after treatment with different concentrations of 8-MOP. Real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Sirt1 is among the most popular target candidates of anti-ER stress, and there are numerous investigations examining this specific Sirt1 role. , Safranal mediates its effect via interaction with NLRP 3 , PTP1B, MAPK, and PI3K . However, little is known about the relationship between Sirt1 and safranal.…”
Section: Discussionmentioning
confidence: 99%
“…Sirt1 is among the most popular target candidates of anti-ER stress, and there are numerous investigations examining this specific Sirt1 role. , Safranal mediates its effect via interaction with NLRP 3 , PTP1B, MAPK, and PI3K . However, little is known about the relationship between Sirt1 and safranal.…”
Section: Discussionmentioning
confidence: 99%
“…Peiqiang Su et al have suggested that MT may reverse IL-1β-induced impaired chondrogenic differentiation in BMSCs by attenuating activation of the NF-κB signaling pathway [ 67 ]. Several studies have found that targeting increased SIRT1 activity can inhibit NF-κB activation, reducing inflammation and oxidative stress in articular cartilage [ 35 , 68 ]. To examine the relationship between MT and the SIRT1/NF-κB pathway, we introduced the SIRT1 inhibitor EX527.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes containing DMEM-F12 and 10% FBS were in the control group and were induced with 10 ng/mL IL-1β for 24 h as the model group. The MT group was induced with 10 ng/mL IL-1β and different concentrations of MT (100, 200, 400, 800 ng/mL) for 24 h. The inhibitor group was treated with 10 ng/mL IL-1β, MT (800 ng/mL), and SIRT1 inhibitor EX527 (20 uM) for 24 h [ 35 ]. Half an hour after adding the lysate, it was transferred to a centrifuge tube and centrifuged at 12,000 rpm for 15 min at 4 °C, and the supernatants of each group were collected.…”
Section: Methodsmentioning
confidence: 99%
“…In osteoarthritis model mice, they found that 8‐MOP promotes AMPKɑ phosphorylation and inhibits NF‐κB phosphorylation through SITR1/NF‐κB pathway and enhances sirtuin‐1 (SITR1) expression, thereby alleviating the symptoms of pain and oxidative stress response (Li, Zhang, Qiu, & Huang, 2021). Also, 8‐MOP reduced inflammatory factors in chondrocytes by interfering with IL‐1β‐mediated apoptosis.…”
Section: Pharmacological Effects Of Xanthotoxinmentioning
confidence: 99%
“…A large number of studies have shown that coumarin components have good antioxidant capacity, and oxidative stress is characterized clinically by impairment in the production and removal of reactive oxygen species(Reilly, Troester, Tyner, Vitale, & Risher, 2010), resulting in diseases such as osteoarthritis and hyperglycemia(Bajerova, Adam, Bajer, & Ventura, 2014;Zhang, Wong, Zhang, Ni, & Li, 2014). The antioxidant pathway of XAT is mainly through scavenging free radicals and prooxidant metal ion chelation, while inhibiting enzyme activity to maintain the level of reactive oxygen species at routine levels.In osteoarthritis model mice, they found that 8-MOP promotes AMPKɑ phosphorylation and inhibits NF-κB phosphorylation through SITR1/NF-κB pathway and enhances sirtuin-1 (SITR1) expression, thereby alleviating the symptoms of pain and oxidative stress response(Li, Zhang, Qiu, & Huang, 2021). Also, 8-MOP reduced inflammatory factors in chondrocytes by interfering with IL-1βmediated apoptosis.…”
mentioning
confidence: 99%